Implementing Constructivism Theory of SKI Lesson - M Dzikrul Hakim Al Ghozali; Siti Illiyun Nisa (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to describe the application and factors that influence the application of constructivism learning theory in SKI subjects in MA Unggulan KH. Abd. Wahab Hasbulloh Tambakberas Jombang. This research method is qualitative research. Data collection techniques are obtained using: 1) Observation; 2) Interviews; 3) Documentation. Data obtained from research processed by means of triangulation techniques include reducing data, presenting data, then drawing conclusions.. The results of this study showed that the application of SKI learning is based on constructivism theory in MA Unggulan KH. Abd Wahab Hasbulloh is the initial activity, the core activity, and the closing activity. In the application of learning using the media playback of movies or videos. The supporting factors are the relevance between the materials, methods, and learning media, and the location of strategic agencies. Then the inhibitory factors are, the lack of confidence in the student, and the lack of time management.